The Effect of Work Motivation, Work Culture and Work Discipline on ASN Performance in the Regional Secretariat Office of RokanHilir Regency - Andri, Seno (International Journal of Psychosocial Rehabilitation, 2020)
In order to achieve organizational goals, work motivation, work culture and work discipline are needed. The overall image of the government bureaucracy in RokanHilir Regency will be determined by the performance of the State Civil Apparatus working for the organization.TheRokanHilir District Secretariat Office is no exception. To provide good services to the community, the RokanHilir Regency Regional Secretariat Office must have qualified, fast and responsive to human resources in responding to the developing information. Improving the performance of human resources is absolutely necessary, in order to build quality of Human Resources.This study, a quantitative study which research instruments use Multiple Regression where to process data by usingSPSS.The results showed that: (1) Work Motivation Variables had a significant effect on the performance of the State Civil Apparatus Office of the Regional Secretariat of RokanHilir Regency. (2) Work Culture variable has a significant effect on the performance of the State Civil Apparatus Office of the Regional Secretariat of RokanHilir Regency. (3) Work Discipline variable has a significant effect on the performance of the State Civil Apparatus Office of the Regional Secretariat of RokanHilir Regency. (4) Work Motivation, Work Culture, and Work Discipline variables affect the performance of the State Civil Apparatus Office of the Regional Secretariat of RokanHilir Regency.